PROBLEMATIKA PEMBERDAYAAN EKONOMI PENDUDUK MISKIN: Kasus Kredit Pundi di Daerah Istimewa Yogyakarta* - Tukiran Tukiran; Suhatmini Hardyastuti; Mohammad Nuh (Populasi, 2002)
This article presents findings of the research on the evaluation of the program for economic empowerment of the poor, carried out through the mechanism of extending Pundicredit. Research findings indicate that the extension of Pundicredit is yet to achieve the intended objectives. There are some problems encountered in the execution of Pundi credit extension. First and foremost although the Pundicredit had intended to help the poor who own some kind of small business, it couldn’t have reached the properly. Secondly, the red tape employed by the executing regional development bank in Pundi credit is considered time distributing consuming by potential credit beneficiaries. To receive such credit, the future beneficiaries have to have some kind of mortgages as pre-conditions, which by all intense and purposes are hard to fulfill. Thirdly, the guidance has focused more on channeling mechanism than on the much needed of business empowerment. Because of that, the deliverance of Pundi credit as an effort to revitalize the economic function of the poor one should find another appropriate outlet, so the empowerment may be realized.